Donación de órganos en Colombia: consideraciones sociojurídicas en torno a la Ley 1805 del 2016 (2020)
The Colombian Law 1805 of 2016 establishes modifications to the legislation on organ donation, in order to reduce the gap between supply and demand. One of the legal changes introduced is the legal presumption of donation that reverses the current functioning of the donor registry, since all people are now considered donors and the registry becomes representative of the desire to be excluded from that presumption. This normative modification involves legal, economic, and social considerations, which are considered here to establish the legal, economic, and social rationality of the presumption of organ donation. Based on this Law as a unit of analysis, a conceptual development with a sociolegal approach on organ donation is proposed. Its sociological aspects are also taken into account and its normative and constitutional framework is analyzed, as well as some international norms. One of its conclusions is that the norm is rational in legal-economic terms as it corrects, at least in a theoretical way, the imbalance between donors and organ recipients, while protecting fundamental rights and extending the life of the recipient in a dignifying manner, thus complying with constitutional principles.